REGENERASI Rhizophora DI KAWASAN HUTAN MANGROVE DESA SUNGAI RAWA KECAMATAN SUNGAI APIT KABUPATEN SIAK PROPINSI RIAU - Muhammad Hamid; Khairijon '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This study aimed to determine the regeneration of Rhizophora on mangrove forest, Sungai Rawa village, Sungai Apit Sub-District, Riau Province. This study had been carried out in February 2014. The sampling were collected with purposive sampling using nested plot. The size of plot for tree, pole, and sapling were 20x20 m, 5x5 m and 2x2 m, respectively. Three locations were selected for study sites, i.e. low, mid, and high activity locations. The result showed that only one Rhizophora spesies i.e Rhizophora apiculata,that found in all of the locations with 300% Important Value Index for each growth stage. R. apiculata had good regeneration status. The highest density in each stage was found in the low activity location, with the density value for seedling, sapling and tree were 17000 individuals / ha, 1200 individual/ha and 318 individual / ha, respectively. While the lowest density was found in different study sites, i.e. high activity location for seedling (3600 individual/ha) and in the mid activity location for sapling (660 individual/ha) and trees (108 individual/ha).